CURRENT STATE AND DEVELOPMENT PROSPECTS OF THE UKRAINIAN DANUBE REGION IN THE POST-WAR PERIOD - KUKHARSKA, Nataliia (Herald of Khmelnytskyi National University. Economic sciences, 2023)
There is an economic analysis of the development of the port and logistics infrastructure of the Danube region of the Odessa region, through which the following objects passes: the Pan-European International Transport Corridor (ITC) No. 7 (along the Danube River); MTC "Europe-Caucasus-Asia" (TRACECA); deep-sea shipping route “Danube – Black Sea”; The free economic zone (FEZ) “Reni” is located on the basis of the Reni ICC, the Euroregion “Lower Danube”. After the beginning of Russia’s full-scale war against Ukraine and the blocking of the ports of “Great Odesa” (Odesa, Chernomorsk, Yuzhny), where the trade turnover decreased twice, the ports of the Danube region became an alternative, that in 2022 increased their trade turnover by 3 times compared to 2021 (including Izmail - 2.2 times, Reni - 6.5 times, Ust-Danube - 12.2 times), making it possible to diversify the main routes of Ukrainian agricultural exports (grain, corn, sunflower oil , rapeseed) and import of finished products. The destruction of the infrastructure of the Danube ports is shown as a result of air attacks by the Russian Federation after withdrawing the “grain agreement” in order to completely remove Ukraine from the world grain markets and thereby gain a monopoly on them. To improve the functioning of the Danube region in the post-war period, important directions for the development of ports are presented, which consist in strengthening the security of existing infrastructure facilities, as well as during the design and construction of new facilities; construction of a new Izmail-Reni railway section to ensure stable freight traffic between the two international transport hubs; construction of a bridge across the Danube in the area of the Orlovka-Isaccea ferry crossing from the point of view of diversifying transport routes for road transport on the border with Romania; strengthening cross-border cooperation with Romania, including the integration of the region with the Galati and Reni SEZs. The main activities have been outlined on the basis that makes possible to create modern logistics centers that will ensure sustainable transit cargo flows between Europe and Asia through the territory of Ukraine.